DEVELOPING ENGLISH READING MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF MARITIME DEPARTMENT OF SMK PELAYARAN SAMUDERA INDONESIA - Jovie Asyrof; Sumarsih Sumarsih; Masitowarni Siregar (Universitas Negeri Medan, 2018)
This research was aimed to develop suitable English reading materials for the eleventh grade students of Maritime Department of SMK Pelayaran Samudera Indonesia. Due to the result of this research was in the form of a product, this research was categorized as Research and Development (R & D) which adapted Borg and Gall (2003) theory with some modifications. The subjects of this research were the eleventh grade students of Maritime Department of SMK Pelayaran Samudera Indonesia. In conducting this research, the procedures were gathering the data and information, conducting the need analysis, designing the first draft of materials, validating by the expert, revising the materials, and producing the final product. The instruments of collecting the data were the combination of two strategies; interview and questionnaires. The interview was analyzed as qualitative data and the questionnaires were analyzed as quantitative data. These data were the needs of students which covered target needs and learning needs. This research only focused on developing two genres of English reading materials based on KTSP that were taught in the second semester which were procedure and analytical exposition. Keywords: English Reading Materials, English for Specific Purposes, Research & Development (R & D), Maritime Department.